THE OPTIMIZATION OF ACCREDITATION DOCUMENTS FOR THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AT SUGIO MUHAMMADIYAH CLINIC, LAMONGAN: OPTIMALISASI DOKUMEN AKREDITASI UNTUK MEWUJUDKAN GOOD CORPORATE GOVERNANCE DI KLINIK MUHAMMADIYAH SUGIO, LAMONGAN - Vica Rahmawati, Nahardian; Tiara Putri Utomo, Dias; Eko Martini, Diah; Nur Diana, Fara; Ummah, Faizatul; Ganda Saputra, Muhamad (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: In 2023, Sugio Muhammadiyah Clinic embarked on an accreditation program, encountering challenges pertaining to the preparation of strategic plan documents, Standard Operating Procedures (SOPs), and quality assessment documents. Objective: To optimize the accreditation documents of Sugio Muhammadiyah Clinic to foster good corporate governance. Method: The study encompassed three primary stages-preparation, implementation, and evaluation-spanning from July to September 2023. A workshop on September 11, 2023, then group discussions on September 12, 2023. A cohort of 24 medical staff members, comprising nurses, doctors, pharmacists, and medical records officers from Sugio Muhammadiyah Clinic, actively participated in these endeavors. Results: Evaluation of the community service was conducted through pre-test and post-test assessments, revealing a noteworthy 35% increase in participants' knowledge of accreditation document preparation. The pre-test mean score was 66.67, with the highest score recorded at 76, while the post-test mean score increased to 90, with the highest score reaching 100. These findings underscore the effectiveness of the community service in enhancing participants' understanding of accreditation document preparation. Conclusion: The community service was successfully carried out to improve participants' knowledge of preparing accreditation documents. It is anticipated that well-crafted accreditation documents will underpin good corporate governance at Sugio Muhammadiyah Clinic, thereby enhancing patient care services.